The effect of a proposed program for developing coordination skills related to the skill performance level of forward roll and front balance beam in gymnastics for female students. (Researcher) - Othman, Asst.LDalkhwaz Hamid Othman (Sulaimani Journal for Humanities, 2025)
To identify the coordination abilities associated with the skill performance level of the forward roll and front balance on the balance beam. To develop a proposed program for enhancing the coordination abilities associated with the skill performance level of the forward roll and front balance on the balance beam for female students. To reveal the effect of the proposed program on developing the coordination abilities associated with the skill performance level of some balance beam skills for female students. The experimental method was used with a two-group experimental design, one experimental and one control group, following pre- and post-testing for each. The research sample was selected purposively from second-year students (2020/2021), totaling (21) students. (1) student was excluded as her assessment was incomplete. The sample was divided into two equivalent groups, one experimental and one control. The educational program was intentionally designed, with the experimental group implementing the proposed program for developing coordination skills, while the control group underwent the same lessons without coordination skills training. The researcher reached the following conclusions: 1- The proposed program for developing coordination skills was effective in improving the skill performance level of the forward roll and front balance on the balance beam in gymnastics for the students. 2- The program used (for the control group) was effective in improving the skill performance level of the forward roll and front balance on the balance beam in gymnastics for the students. 3- The proposed program for developing coordination skills was more effective than the program used (for the control group) in improving the skill performance level of the forward roll and front balance on the balance beam in gymnastics for the students. 4- The experimental group showed higher post-test improvement rates than the control group in both coordination skills and skill performance level for the forward roll and front balance on the balance beam in gymnastics for the students.
Keywords: Skillful performance; balance beam; gymnastics